Extending cellulose-based polymers application in additive manufacturing technology: A review of recent approaches - Mohan D.; Teong Z.K.; Bakir A.N.; Sajab M.S.; Kaco H. (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA